A Note on Predefined-Time Stability⁎. Issue 13 (2018) - Jiménez-Rodríguez, Esteban; Muñoz-Vázquez, Aldo Jonathan; Sánchez-Torres, Juan Diego; Loukianov, Alexander G.
Abstract: This note presents a new characterization for predefined-time-stable systems based on Lyapunov stability. In contrast to the previous results in predefined-time stability, the proposed characterization allows the construction of predefined-time stabilizing controllers with polynomial terms instead of exponential ones, removing the exponential nature hypothesis of predefined-time-stable systems. Moreover, the existing Lyapunov characterization of predefined-time stability is shown to be a consequence of the new theorem presented in this paper. Finally, the proposed approach is used for the construction of robust predefined-time stabilizing controllers for first-order systems. A simulation example shows the feasibility of the proposed methods.